2018
DOI: 10.3390/e20050310
|View full text |Cite
|
Sign up to set email alerts
|

Exergy Analyses of Onion Drying by Convection: Influence of Dryer Parameters on Performance

Abstract: This research work is concerned in the exergy analysis of the continuous-convection drying of onion. The influence of temperature and air velocity was studied in terms of exergy parameters. The energy and exergy balances were carried out taking into account the onion drying chamber. Its behavior was analyzed based on exergy efficiency, exergy loss rate, exergetic improvement potential rate, and sustainability index. The exergy loss rates increase with the temperature and air velocity augmentation. Exergy loss … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…EUR for the drying of rosemary samples was calculated using Equation (22), and its average values ranged from 0.246 to 0.502. Table 2 presents the average changes in EUR with temperature and air velocity.…”
Section: Energy Utilization Ratio (Eur)mentioning
confidence: 99%
See 1 more Smart Citation
“…EUR for the drying of rosemary samples was calculated using Equation (22), and its average values ranged from 0.246 to 0.502. Table 2 presents the average changes in EUR with temperature and air velocity.…”
Section: Energy Utilization Ratio (Eur)mentioning
confidence: 99%
“…Several studies have been undertaken using exergy and energy analysis of the drying processes of crops, such as potato slices in a continuous band dryer [14], rice in a convective dryer [15], mushroom slices in a hot air dryer [16], bananas in convective dryers [17,18], parboiled paddy rice in a LSU industrial dryer [19], drying corn in a new industrial dryer system [20], carrots in a convective dryer [21], onions in a convective dryer [22], turmeric in forced convection solar tunnel dryers [23,24], and carob pulp in a solar collector dryer [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, heat lost from the dryer body can be another reason of low exergy efficiency. [67] It is worth noting that exergy lost from the dryer body happened when the body temperature was higher than the ambient temperature. Thus, heat transfer isolation can effectively reduce exergy losses from the body.…”
Section: Exergy Efficiencymentioning
confidence: 99%
“…They found that the exergy loss rates increases with the temperature and air velocity augmentation and the exergy efficiency increases with the air velocity augmentation. 28 The energy needed for drying depends on the nature of the product, its initial and final moisture contents and drying rate. Thus energy and exergy analysis needs to be carried out in order to quantify the energy needed for drying and to locate the exergy losses in the system.…”
Section: Introductionmentioning
confidence: 99%